Sports Skills and Values in West Java Taekwondo Athletes - Nugraha, Taufik Krisna; Sutresna, Nina; Mulyana, Mulyana (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
Sport has a very broad meaning, not just defined as mere physical activity or even just for achievement, sport can also improve one's life skills. The purpose of this research is to determine the sports skills and values of West Java Taekwondo athletes. This research method is descriptive quantitative with a cross-sectional research design. This study uses a questionnaire instrument of sports skills and values adapted from Cronin & Allen, (2017), de Subijana et al., (2020) and United Nations, (2003) reliability level of 0.951. There are 23 indicators: cooperation, playing honestly, communication, sharing, respect for rules, self-esteem, solving problems, trust, understanding, honesty, connecting with others, respecting yourself, leadership, tolerance, mutual respect, joy and perseverance, hard work, teamwork, strategies to win, discipline, strategy if you lose, self-confidence, and how to organize matches. The population of this research was West Java taekwondo athletes, then the purposive sampling approach was used with several sample criteria. This sample consists of 125 athletes with the following criteria: (1) taekwondo athletes in West Java who have received an intensive training program, (2) age levels between 14-30 years, (3) have practiced taekwondo for at least 2 years, (4) belt level minimal yellow. The conclusion of this study shows that the percentage of sports skills and values of athletes in West Java is in two criteria, namely the first criteria are 103 athletes including moderate criteria, 44 athletes with high criteria.